GOVERNMENT COALITION PARTIES' INTEREST CONFLICT AND THEIR ETHICS BASED ON SURAH AL-MUMTAHANAH - Iman, Sunardi Bashri (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2024)
A multi-party system of governance, which is based on idiosyncratically and culturally diverse identities, is so prone to disintegration that it will erode public trust. Government confidence and authority declined as a result of problems that emerged as government coalitions were formed. The most notable of these included the rejection of influence, the politicization of the law, the arrogance of officials, the repudiation of offices, and the accumulation of wealth in unwarranted ways. The author's motivation to solve the formula problem,